MAPPING IPSO-FACTO “UAF” ROLE IN PAKISTAN’S AGRICULTURE DEVELOPMENT: (AN ANALYSIS) - ASIFA TARIQ ,; Dr. Rana Danish Nisar,; Hamid Iqbal, (Journal of Peace, Development and Communication, 2023)
The agricultural industry holds the largest share in Pakistan's economy. The educational and research endeavors of the University of Agriculture Faisalabad have significantly influenced the agricultural growth of Pakistan. The University of Agriculture Faisalabad (UAF) has made significant contributions to research both domestically and internationally. The University of Agriculture Faisalabad (UAF) has implemented innovative methodologies within the agricultural sector to foster the advancement of Pakistan's economy. The study scope is highly extensive on a worldwide scale. The University of Agriculture Faisalabad (UAF) has implemented novel technological advancements within agricultural settings to enhance crop output. In the present setting, a diverse range of research extensions conducted by the University of Agriculture Faisalabad (UAF) have been implemented with the aim of augmenting the agricultural productivity inside the nation. The dissemination of information and technology to rural communities has been effectively achieved through the publication of research articles in both national and international publications. The University of Agriculture Faisalabad (UAF) plays a significant and vital role in fostering the agricultural and industrial advancement of Pakistan. The University of Agriculture Faisalabad (UAF) plays a significant role in disseminating cutting-edge technological information to individuals engaged in agricultural practices, hence facilitating their contribution to the economic development of Pakistan. Examining the current state of the nation, it is evident that the literacy rate is experiencing gradual growth. Given this context, it can be asserted that the University of Agriculture Faisalabad (UAF) holds significant potential in contributing to the agricultural advancement of Pakistan, hence facilitating the provision of enhanced services to both small-scale and large-scale farmers.